KAJIAN TIPOGRAFI, RUANG, DAN WARNA DALAM MEMBENTUK ESTETIKA PADA LOGO FEDEX - Puspitasari, Fani; Diningrat, Nahdiyan Raja (CREATIVA SCIENTIA, 2025)
FedEx is a delivery service company that operates in many countries or commonly called multinational. This research aims to examine the elements of typography, space, and color in forming aesthetics in the FedEx logo using descriptive qualitative methods. Data collection is done by making indirect observations through the internet and then studied with Dharsono's aesthetic principles approach through three elements namely typography, space and color. From this principle, space is related to visual gestalt theory which proves that to recognize or “read” an image, a contrast between positive space called figure and negative space called ground is needed. This then forms the perception of a shape or pattern between the letters E and x, namely an arrow that can represent the image of FedEx as a fast delivery service.